Therapeutic effects of short-term supplementation of 0.5 and 1.0% pineapple shell on rabbits with experimentally induced osteoarthritis - Korakot Nganvongpanit (2018)
Treatment of osteoarthritis using bromelain has been widely utilized; however, the cost of bromelain is expensive because high technology is required for its extraction from pineapple. Therefore, in the present study dry pineapple shell at 0.5 and 1.0% was exploited as a dietary supplement for rabbits with experimentally induced osteoarthritis. Gene and protein expression, biomarker levels and histopathological scores were used to evaluate the effect of pineapple shell on osteoarthritis treatment. The results showed no significant difference (P > 0.05) in the level of biomarkers and histopathological scores among three groups (non-treated control, and daily oral administration of 0.5 and 1.0% dry pineapple shell). The relative expressions of TIMP-1, MMP-1 and MMP-3 were significantly different between the 1.0% dry pineapple shell group and the control group. Daily oral administration of 1.0% pineapple shell for 3 months could alter the expression of anabolic genes; but this level was not sufficient for improving biomarker levels and histological scores. Supplementation with higher dosages and for longer periods of time should be considered before performing future clinical trials.